Carbapenemase-Producing Bacteria from Urinary Tract Infection (UTI) Cases at University College Hospital, Ibadan, Nigeria.Carbapenemase-Producing Bacteria from Urinary Tract Infection (UTI) Cases at University College Hospital, Ibadan, Nigeria - AZEEZ, Mufutau Mosunmade, OGUNDELE, Daniel Feranmi, ALADE, Wakeel Adekunle, AKINLABI, Akinwale Majid, OLANIYAN, Mathew Folaranmi. (Sokoto Journal of Medical Laboratory Science)
Urinary Tract Infections (UTIs) caused by Carbapenemase-producing bacteria (CPB) have become a substantial public health concern due to their increasing prevalence and resistance to antibiotics leading to challenges in treatment. The increase in the number of antibiotics that these bacteria are resistant to limits the options available to achieve effective therapy for these infections. The aim of this study was to assess the occurrence of Carbapenemase production among bacterial isolates from UTI cases, analyze antibiotic susceptibility profiles, and investigate the prevalence and diversity of bacterial pathogens in UTI cases at University College Hospital, Ibadan. A total of 126 participants, comprising of 68 females (54%) and 58 males (46%) with age range of 18 – 85 years, were enrolled in the study. About 20 mls of mid-stream urine sample collected into sterile plastic universal bottles was received from each of the consenting participants and processed for microscopy, culture, isolates identification, antibiogram testing and carbapenemase production using standard procedures. The prevalence of Carbapenemase-producing bacterial isolates among the study participants was found to be 9.2%. Notably, the prevalence of Carbapenemase production was observed to be higher among males with UTI, accounting for 62.5% of the cases compared to 37.5% in females. C o m p a r a t i v e a n a l y s i s b e t w e e n n o n - Carbapenemase-producing and Carbapenemase-producing bacterial isolates revealed significant impact of socio-demographic factors such as age and gender. Significant difference in prevalence was observed, particularly within the 30-45 and 45-60 age groups, signifying notable variations between the two age groups (P<0.05). However, gender distribution did not show statistically significant differences overall (p>0.05). The predominant bacterial uropathogens isolated from UTI cases included Escherichia coli (47%), Klebsiella pneumoniae (26%), and Pseudomonas aeruginosa (16%). Among Carbapenemase-producing bacterial isolates, Klebsiella pneumoniae showed the highest prevalence (37.5%), followed by Escherichia coli and Pseudomonas aeruginosa, each at 25%. The findings revealed a significant occurrence of Carbapenemase in the uropathogens frequently involved in UTI. The implications of these findings underscore the critical role of carbapenems as last-resort antibiotics and highlight the urgency in controlling the spread of Carbapenemase-producing organisms within the c o m m u n i t y. T h e o b s e r v e d r a t e s o f carbapenemase-producing bacteria (CPB) among UTI patients echo similar trends reported in studies from other regions, emphasizing the global significance of this issue and the need for robust strategies to mitigate the dissemination of multidrug-resistant bacteria in healthcare settings. This study serves as a crucial indicator of the prevalence of Carbapenemase-producing bacteria in UTI cases at University College Hospital, Ibadan, and emphasizes the imperative for concerted efforts in infection control measures and antibiotic stewardship to combat the rising threat of antimicrobial resistance.